(untitled) (Sustainability in Debate, 2023)
The value of a good is not something fixed and objectively given but results from social valuation processes in which value is constructed. This process is fundamental for the functioning of markets, as they depend, among other things, on the ability of social actors to evaluate the qualities of goods and compare them in terms of value. In this way, the valuation process considers different criteria that often compete. The significant growth in the sale of electric cars in Brazil points to the formation of a market niche, with consumers willing to invest in new propulsion technologies, which, in theory, are more sustainable than conventional cars. From this context, the research seeks to investigate, through interviews with owners, the role of symbolic values in qualifying "sustainable" goods, such as electric cars. Data analysis points to the mobilisation of functional and symbolic values, although imaginatively appropriate, as fundamental criteria for the acquisition of cars.